Toxicity Study Of Isoprothiolane On Macrobrachium Lanchesteri In Surface Water Of Paddy Field Ecosystem - Rahman, Muhammad Radzi Abd (2019)
The application of isoprothiolane in rice cultivation may give risk to the aquatic ecosystem. The present study was undertaken to determine the level of isoprothiolane in surface water of paddy fields and consequently, to determine the acute and chronic toxicity level of isoprothiolane to freshwater prawn, Macrobrachium lanchesteri. LC50 or lethal concentration for 50 percent mortality in population was used as the endpoint for acute toxicity level while for chronic, no-observed effect concentration (NOEC) is preferable. Prediction on chronic toxicity level was determined using assessment factor and two-step linear regression (LRA) method. The predicted no-observed effect concentration (PNEC) was compared to the NOEC value from 21 days chronic test to determine the conservativeness between the prediction and the experimental value. Water samples from 12 sampling points were collected from sampling sites and extracted by solid phase extraction method. The samples were then analysed by gas chromatography-mass spectrometry (GC-MS) to quantify the concentration of isoprothiolane detected in the samples. Isoprothiolane residue was detected in both the vegetative stage (maximum tillering) and ripening stage of paddy growth. The concentration of isoprothiolane residue found in the ripening stage was higher than in the vegetative stage. The highest amount of isoprothiolane residue detected was at 9.37 mg/L from water sample collected at sampling point 5 (S5) at the ripening stage. LC50 of isoprothiolane on M. lanchesteri was determined after 96 hours of exposure, interpreted by Probit analysis from SPSS software.